Benjamin Franklin, scientist-diplomat - Daugherty, Charles Michael; Falter, John Philip, 1910- (New York : Macmillan, 1965)
The life story of Benjamin Franklin highlights his diplomatic ability, his work as printer and inventor, and his many scientific achievements and experiments, including the famous kite experiment.
Keywords: Franklin, Benjamin, -- 1706-1790 -- Juvenile literature; Franklin, Benjamin, -- 1706-1790.; Franklin, Benjamin, -- 1706-1790.; Statesmen -- United States -- Biography -- Juvenile literature; Scientists -- United States -- Biography -- Juvenile literature; Statesmen; Scientists; Statesmen -- United States -- Biography; Scientists -- Biography